Essays on multidimensional poverty and gender in Brazil - Batista, Andrezza Luiza (2023)
This thesis is dedicated to studying Brazil's multidimensional poverty with a gender focus. Specifically, we consider poverty a phenomenon that affects people’s live’s in several aspects other than income, such as education, employment, and living conditions. Also, we consider that poverty is driven differently by men and women due to social, economic, and cultural gender differences. Hence, the first essay aimed to analyze the multidimensional poverty in Brazil with a breakdown of gender, race, and regional disparities. To do so, a Multidimensional Poverty Index was constructed with eleven indicators (years of schooling, literacy, employment, income, electricity, sanitation, water, garbage disposal, cooking fuel, assets, and overcrowding) within four dimensions (education, employment, income, and living standards). We used data from the National Household Sample Survey (PNAD) from 2004 to 2015. The results found in this chapter indicated that women have higher deprivation than men. They are the majority of people experiencing poverty and suffer a more intense form of poverty than men. Black women and the ones living in rural areas are in a situation even worse. We also found that employment and income are the dimensions that drive multidimensional poverty in Brazil and that women in Brazil have difficulty transforming education into income. Additionally, results showed that women’s poverty has been reducing slower than men’s. The second essay analyzed whether migration and nonagricultural jobs can be seen as pathways out of multidimensional poverty for individuals from rural Brazil, breaking it down by gender. The relationship between livelihood strategies and multidimensional poverty was estimated by a two-stage least squares estimation considering extreme climate events in temperature and precipitation as instruments for migration and nonfarm performance since they can be considered endogenous. The data used was also the National Household Sample Survey (PNAD) from 2004 to 2015. We used the deprivation score calculated by the Multidimensional Poverty Index method for the dependent variable. The results of this paper suggest that performing nonagricultural activities can act as pathways out of poverty in rural Brazil, reducing deprivation, but only for men, and that migration is irrelevant in explaining the changes in deprivation. In general, this thesis contributes theoretically and empirically to understanding several facets of poverty in Brazil. Keywords: Multidimensional poverty. Deprivation. Gender.